Little women - Alcott, Louisa M. (Penguin Harmondsworth, Middlesex, 1994)
'Little Women' is recognised as one of the best-loved classic children's stories of all time. Originally written as a 'girls' story', its appeal transcends the boundaries of time and age, making it as popular with adults as it is with young readers